Microbial Biofilms Colonizing Plastic Substrates in the Ross Sea (Antarctica) - Carmela Caroppo; Maurizio Azzaro; Ombretta Dell’Acqua; Filippo Azzaro; Giovanna Maimone; Alessandro Ciro Rappazzo; Francesco Raffa; Gabriella Caruso (Journal of Marine Science and Engineering, 2022)
Very few studies have investigated marine microbial colonization in polar regions, but climate-changing scenarios stress the importance of these investigations to protect life in such extremely vulnerable ecosystems. In two different coastal sites of the Ross Sea (Road and Tethys Bays, Antarctica) exposed to different stressors, the microbial biofilm colonizing the surface of plastic (polyvinyl chloride, PVC, and polyethylene, PE) panels left submerged in two experiments at different timescales (“short-term”: 3 months, and “long-term”: 9 and 12 months) was studied. The abundance and metabolic enzymatic activities [leucine aminopeptidase (LAP), beta-glucosidase (GLU) and alkaline phosphatase (AP)] of the prokaryotes and the microalgal abundance and species composition were analyzed, in parallel with the main environmental parameters. The prokaryotic community showed higher abundance and metabolic activities on PVC than on PE as opposed to microalgae. A peak in the microfouling prokaryotic abundance and metabolic functions was frequently recorded after 3 months of immersion, corresponding to the late austral summer period. LAP and AP were the most active enzymes, suggesting that microbial metabolic profiles were modulated by labile organic substrates. Our results suggest that the composition and function of microbial biofilm could be considered as sentinels of natural or anthropic-related disturbances.